1999
DOI: 10.1091/mbc.10.5.1653
|View full text |Cite
|
Sign up to set email alerts
|

Coiled Bodies Preferentially Associate with U4, U11, and U12 Small Nuclear RNA Genes in Interphase HeLa Cells but Not with U6 and U7 Genes

Abstract: Coiled bodies (CBs) are nuclear organelles involved in the metabolism of small nuclear RNAs (snRNAs) and histone messages. Their structural morphology and molecular composition have been conserved from plants to animals. CBs preferentially and specifically associate with genes that encode U1, U2, and U3 snRNAs as well as the cell cycle-regulated histone loci. A common link among these previously identified CBassociated genes is that they are either clustered or tandemly repeated in the human genome. In an effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 43 publications
2
74
0
Order By: Relevance
“…In this scheme, the free coilin present in the nucleoplasm (~70% of the total pool) could associate with individual Sm/Lsm proteins and bring them back to CBs. There a limited amount of snRNP reassembly or even de novo assembly could take place, as the SMN complex is also present and several snRNA genes are frequently associated with CBs Matera 1995, 2001;Jacobs et al 1999;Schul et al 1998;Smith et al 1995). Alternatively, SMN could take over such reclaimed Sm/Lsm proteins at the CBs and return them to the cytoplasm where they could be reused in the assembly of new snRNPs.…”
Section: Discussionmentioning
confidence: 99%
“…In this scheme, the free coilin present in the nucleoplasm (~70% of the total pool) could associate with individual Sm/Lsm proteins and bring them back to CBs. There a limited amount of snRNP reassembly or even de novo assembly could take place, as the SMN complex is also present and several snRNA genes are frequently associated with CBs Matera 1995, 2001;Jacobs et al 1999;Schul et al 1998;Smith et al 1995). Alternatively, SMN could take over such reclaimed Sm/Lsm proteins at the CBs and return them to the cytoplasm where they could be reused in the assembly of new snRNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The only processing event required for formation of histone mRNA is cleavage of the nascent transcript to form the 39 end of histone mRNA+ In the cell, this reaction probably also serves to release the nascent RNA from the chromatin template+ Processing of histone premRNA requires assembly of both SLBP and U7 snRNP on the pre-mRNA )+ Increased expression of either of these factors in frog oocytes stimulates processing of histone pre-mRNA transcribed from an injected gene (Fig+ 1D;Jacobs et al+, 1999;Wang et al+, 1999)+ We have previously shown that the two Xenopus SLBPs have different functions+ xSLBP1 is orthologous to human and mouse SLBP and participates in histone mRNA 39 end formation (Wang et al+, 1999)+ xSLBP2 is expressed only during oogenesis, is degraded after oocyte maturation (Wang et al+, 1999), and may be involved in storing maternal histone mRNA in a translationally inactive form+…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the processing of histone pre-mRNA derived from injected DNA+ A: The S1 nuclease protection assay used to measure histone pre-mRNA processing is diagramed+ The 260-nt probe contains 43 nt that are not present in the H2a-614 histone pre-mRNA, but are derived from the vector pBluescript KS (zig-zag line)+ The unprocessed RNAs protect a 217-nt fragment regardless of their 39 end and the processed histone mRNAs protect a 183-nt fragment+ Because the probe is 39-end labeled, the ratio of the intensity of the two fragments is a measure of processing efficiency+ B: Frog oocytes were preincubated in buffer (lane 2) or with 200 mg/mL Actinomycin D (lane 3) for 1 h+ They were then injected with the histone H2a-614 gene and blue Dextran, and incubated in the continued presence of the inhibitor for 18 h+ RNA was prepared and then assayed for histone H2a-614 mRNA+ Lane 1 is marker pUC18 digested with MspI+ C: Oocytes were injected with the H2a-614 gene and blue Dextran, incubated for 18 h and then half of the oocytes were harvested (lane 1) and the other half were incubated for an additional 5 h in 200 mg/mL Actinomycin D (lane 2)+ A separate batch of oocytes was injected with either the H2a-614 gene (lane 3) or with the histone H2a-4G gene (lane 4) and incubated for 18 h+ The H2a-4G gene produces a transcript that cannot be processed because of the insertion of four Gs at the cleavage site )+ RNA was prepared from the oocytes and RNA from the equivalent of one oocyte analyzed by S1 nuclease mapping+ D: Frog oocytes were injected with the histone H2a-614 gene and the levels of processed and unprocessed histone mRNAs measured 18 h later (lane 1)+ In lane 2, the human U7 gene (Jacobs et al+, 1999) was coinjected into the nucleus with the H2a-614 gene+ In lane 3 the oocytes were injected with synthetic xSLBP1 mRNA 30 h prior to injection of the histone H2a-614 gene+ In lane 4, the oocytes were injected with the xSLBP1 mRNA 30 h prior to coinjection of the human U7 gene and the histone H2a-614 gene+ The processing efficiency (percent processing) quantified using a PhosphorImager is indicated below each lane+ xSLBP1 and U7 snRNP cooperate to process histone pre-mRNA in vivo Histone pre-mRNA processing in oocytes requires both xSLBP1 (Wang et al+, 1999) and the U7 snRNP (Scharl & Steitz, 1996) as well as other factors+ A critical step in vitro is assembly of a stable complex containing SLBP and U7 snRNA on the histone pre-mRNA , and efficient assembly of the complex requires both stable binding (high affinity) of SLBP to the stem-loop and base-pairing of U7 snRNP to the pre-mRNA )+ To determine whether xSLBP1 or U7 snRNP were limiting for processing in vivo we increased the concentration of U7 snRNA by expressing U7 snRNA from the human U7 snRNA gene (Jacobs et al+, 1999) and the concentrations of xSLBP1 by injecting synthetic xSLBP1 mRNA+ There are excess snRNP proteins present in the frog oocyte that will assemble U7 snRNA into functional U7 snRNP particles (Strub & Birnstiel, 1986)+ In this experiment we used a batch of oocytes that processed the histone H2a-614 mRNA relatively inefficiently (Fig+ 1D, lane 1)+ Overexpression of either U7 snRNA or xSLBP1 resulted in an increased efficiency of processing (Fig+ 1D, lanes 2 and 3)+ Overexpression of both xSLBP1 and U7 snRNA in the same oocytes resulted in a further increase in processing (Fig+ 1D, lane 4)+ Thus both U7 snRNP and xSLBP1 are present at suboptimal concentrations for processing the histone H2a-614 pre-mRNA expressed in the oocyte+ This result is consistent with the suggestion that these two factors cooperate in histone pre-mRNA processing …”
Section: Unprocessed Histone Mrna Is Stable In Xenopus Oocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…90,91,95,100 Cajal bodies consistently associate with specific loci on multiple chromosomes, many of which include snRNA gene arrays, snoRNAs, as well as other small U RNA and histone gene clusters. 11,12,[118][119][120] Following siRNA knockdown of essential Cajal body components, WDR79/WRAP53 or USPL1, these chromosomal regions were no longer clustered, and the expression of many of the associated small U RNA loci were significantly reduced. Thus, disruption of Cajal bodies leads to a loss of genome conformation and this may lead to inefficient expression of snRNAs.…”
Section: Smn and Cajal Body Structurementioning
confidence: 99%